Incidence and risk factors for hospital-acquired infection among paediatric patients in a teaching hospital: a prospective study in southeast Ethiopia. Issue 12 (17th December 2020) - Sahiledengle, Biniyam; Seyoum, Fekadu; Abebe, Daniel; Geleta, Eshetu Nigussie; Negash, Getahun; Kalu, Abdurhaman; Woldeyohannes, Demelash; Tekalegn, Yohannes; Zenbaba, Demisu; Edward Quisido, Bruce John
Abstract : Objectives: In order to maximise the prevention of hospital-acquired infections (HAIs) and antimicrobial resistance, data on the incidence of HAIs are crucial. In Ethiopia, data about the occurrence of HAIs among hospitalised paediatric patients are lacking. We aim to determine the incidence and risk factors of HAIs among paediatric patients in Ethiopia. Design: A prospective cohort study. Setting: A teaching hospital in southeast Ethiopia. Participants: 448 hospitalised paediatric patients admitted between 1 November 2018 and 30 June 2019. Primary and secondary outcome measures: Incidence and risk factors of hospital-acquired infections. Results: A total of 448 paediatric patients were followed for 3227 patient days. The median age of the patients was 8 months (IQR: 2–26 months). The incidence rate of HAIs was 17.7 per 1000 paediatric days of follow-up; while the overall cumulative incidence was 12.7% (95% CI 9.8% to 15.8%) over 8 months. Children who stayed greater than 6 days in the hospital (median day) (adjusted risk ratio (RR): 2.58, 95% CI 1.52 to 4.38), and children with underlying disease conditions of severe acute malnutrition (adjusted RR: 2.83, 95% CI 1.61 to 4.97) had higher risks of developing HAIs. Conclusions: The overall cumulative incidence of HAIs was about 13 per 100 admitted children. Length of stay in the hospital and underlying conditions of severe acute malnutrition were found to be important factors associated with increased risk of HAIs.